THE INFLUENCE OF SOCIAL CLASS TOWARD SOCIAL REJECTION IN NOVEL OF MICE AND MEN BY JOHN STEINBECK - Andika, Mohammad Bagus (Faculty of Letters Universitas Balikpapan, 2026)
The research uses novel Of Mice and Men by John Steinbeck as an object of the research. This research uses Sociology of Literature approach with coverage Social Class by Karl Marx and Social Rejection by Leary and Chandrani Mukherjee. The theories are used in the research those theory Social class by Karl Marx is divided into theory of alienation, false consciousness, class struggle and theory Social Rejection by Chandari Mukherjee. The researcher used Descriptive Qualitative methods that is explaining descriptively based on this research using document analysis as a reference. The result of this research is finding three forms of social rejection, those are social environtment or friendship rejection with 46 data, career or workplace rejection with 14 data, and intimate relationship[ rejection with 5 data. Then, the influence of social class toward social rejection shows the alienation toward social environment or friendship rejection with 24 data, alienation toward workplace and career rejection with 23 data, alienation toward intimate relationship rejection with 5 data. Overall, alienation as an influence of social class toward social rejection has the most excerpts in the three forms of social rejection, especially in form social environment or friendship rejection it is the most rejection.